2013
DOI: 10.2337/dc12-2360
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Real-Time Continuous Glucose Monitoring in Pregnant Women With Diabetes

Abstract: OBJECTIVETo assess whether intermittent real-time continuous glucose monitoring (CGM) improves glycemic control and pregnancy outcome in unselected women with pregestational diabetes.RESEARCH DESIGN AND METHODSA total of 123 women with type 1 diabetes and 31 women with type 2 diabetes were randomized to use real-time CGM for 6 days at 8, 12, 21, 27, and 33 weeks in addition to routine care, including self-monitored plasma glucose seven times daily, or routine care only. To optimize glycemic control, real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 36 publications
5
202
1
4
Order By: Relevance
“…However, current glucose targets for both the diagnosis and treatment of GDM patients still do not have normalized perinatal outcomes (15,16). By way of the 72-h CGM, we were able to assess glucose profiles during the third trimester of GDM patients, as defined by IADPSG (6), and compare them to those of matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current glucose targets for both the diagnosis and treatment of GDM patients still do not have normalized perinatal outcomes (15,16). By way of the 72-h CGM, we were able to assess glucose profiles during the third trimester of GDM patients, as defined by IADPSG (6), and compare them to those of matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors caution that the flattening of glucose variability here observed in the GDM2 group related to dietary counseling might not be enough to favorably affect perinatal outcomes in all patients, due to the importance of other confounders besides glucose, such as obesity, lipids, cytokines, among others (22,23). Future studies should possibly address these changes in the same patients, before and after dietary counseling, although we recognize that it could limit the patient sample according to the protocol (16). Studies conducted on groups at high risk of diabetes, such as other mild or subclinical glucose metabolism disorders, have also observed differences in CGM glucose parameters, suggesting that glucose variability and levels above predefined thresholds seem to be the earliest detectable glucose abnormalities within the range of carbohydrate metabolism disorders (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…An HbA 1c level in pregnancy ,7% (53 mmol/mol) was considered acceptable; thus, HbA 1c levels in our cohort were higher than we would expect today (31). In a Danish study using cognitive scores at conscription, HbA 1c was negatively associated with offspring cognitive function, but when HbA 1c levels were ,7% (53 mmol/mol) cognitive function was the same as in control subjects (23).…”
Section: Maternal Glycemic Controlmentioning
confidence: 91%
“…29 The Danish study of intermittent real-time CGM (rtCGM) found no differences in outcomes between groups; however, only 64% (49/76) in the rtCGM group followed the protocol. 30,31 Taken together, these studies suggest that adjunctive CGM use may help make decisions about therapy, but improvement of long-term glucose control and outcomes may require more than just intermittent use.…”
Section: <6% <6%mentioning
confidence: 99%